PEMANFAATAN ABU SEKAM PADI DAN BATU NAPAL SEBAGAI BAHAN DASAR MORTAR GEOPOLIMER - Eki; Edowinsyah (JURNAL ILMIAH BERING'S, 2020)
Geopolymer mortar is a mortar based mixture without using porland cement as a binding material replanced with rice husk ash and marl, using a mixture of sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) to determine the effect of using huskk ash rice and stone mortar napal geopolymer conducted research using experiment in the laboratory using 5x5x5cm3 specimens the ratio of rine husk ask and stoone marl 75%:25%,50%:50%,25%:75% as much as 45 test specimens, compressive strength testing aged 3, 7, 14, 21, and 28 days. From testing the maximum strength is 17,73 Mpa obtained at the age og 28 days for rice ash and stone marl 25% : 75% from the results of the compressive strength shows that the addition of stone and the reduction of ash made of rice husk compressive strength increases.